Histopathological Study of Streptozotocin Induced Liver Regeneration of Wistar Mice after Administration of Pumpkin Leaf Ethanol Extract - Niluh Puspita Dewi; Windi Olivia Kawanga; Debora Rislianti Lakiu (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2021)
This study aims to prove that the ethanol extract of pumpkin leaf can improve the liver histological structure of Wistar rats streptozotocin and find out the effective dose in regenerating the liver cells of Wistar rats. Wistar rats were divided into six groups so that each group has five replications. The control group was not given the extract, and the treatment group was administered the extract with three doses of 125 mg/kg BW, 150 mg/kg BW, and 175 mg/kg BW which were carried out for three weeks. Rats were then sacrificed and the liver organs were taken for the histopathology preparations with Hematoxylin-Eosin staining (HE). The results showed fatty degeneration and necrosis of the livers. The results of the Mann-Withney test analysis showed that there was a significant difference in liver histopathology scoring from each treatment group. Ethanol extract  of pumpkin leaves at a dose of 150 mg/kg BW gave an effect on the  regeneration of liver cells of Wistar rats with a damage score of 1.4 and had no effective dose